Scanning electron microscopy and energy-dispersive X-ray spectroscopy on the degree of bone mineralization at the bone-implant interface - Ilinca Antigona Iancu; Stefania Andrada Iancu; Dragos Epistatu; Monica Comaneanu; Ioana Anca Badarau (Amaltea Medical Publishing House, 2024)
Background. The purpose of this research was to evaluate the degree of mineralization as well of the chemical composition at the interface of failed dental implants with surrounding bone. Material and methods. The analysis was performed on human histological samples by the aid of a scanning electron microscope and an energy-dispersive x-ray spectroscopy (ESEM-EDX). Results. The middle and the apical region of the implant surfaces had higher quantity of bone tissue deposition. A higher degree of mineralization was observed in these two regions as well. Conclusion. From the analysis performed by the aid of scanning electron microscopy, it appears that the bone tissue deposition is better represented in the middle and apical region of the implants.